Responsibility and the Moral Phenomenology of Using Self-Driving Cars. Issue 8 (13th September 2016) - Coeckelbergh, Mark
ABSTRACT: This paper explores how the phenomenology of using self-driving cars influences conditions for exercising and ascribing responsibility. First, a working account of responsibility is presented, which identifies two classic Aristotelian conditions for responsibility and adds a relational one, and which makes a distinction between responsibility for (what one does) and responsibility to (others). Then, this account is applied to a phenomenological analysis of what happens when we use a self-driving car and participate in traffic. It is argued that self-driving cars threaten the excercise and ascription of responsibility in several ways. These include the replacement of human agency by machine agency, but also the user's changing epistemic relation to the environment and others, which can be described in terms of (dis)engagement. It is concluded that the discussion about the ethics of self-driving cars and related problems of responsibility should be restricted neither to general responsibilities related to the use of self-driving cars and its objective risks, nor to questions regarding the behavior, intelligence, autonomy, and ethical "thinking" of the car in response to the objective features of the traffic situations (e.g. various scenarios). Rather, it should also reflect on the shifting experience of the user: how the new technology reshapes the subjectivity of the user and on the morel consequences this has.